Essay on a PositHIVe Museology (Cadernos de Sociomuseologia, 2021)
AIDS marked the 1980s as the greatest epidemic of modern times and through it revealed several points of social, political, religious and even economic tension. Because of its transmissibility through sex and blood, HIV developed its history through moralism and symbolism linked to its transmission routes, which generated the stigma and prejudice found until today when the topic is addressed. In this way, the research seeks to analyze the factors that contributed to the construction of the epidemic's memory, how it influences today the way we face the virus and how museums, memory spaces, can, through their actions, contribute to the deconstruction of stigma and prejudice linked to the disease.Keywords: HIV/AIDS; LGBT Museology; Sociomuseology